Factors Influencing Farmers’ Adoption of Soil Conservation Development - Gara, Anissa; Mhede, Edwin P; Shimada, Sawahiko; Toyoda, Hiromichi (Journal of Social Economics Research, 2020)
Landscape degradation by soil erosion has increased considerably in Ethiopian lands due to deforestation of natural mountain forests and the cultivation of large areas resulting in a serious environmental problem threatening the sustainability of agriculture and population food security. In Boset Wareda (in Ethiopia), farmers are producing for subsistence and exerting an increasing erosion of the land. Nevertheless, soil and water resources degradation addicted by natural and anthropologic activities are usually controlled by soil conservation techniques and water harvesting constructions. This study has contributed knowledge on social, economic and technical factors affecting adoption of CTs among household farmers in Ethiopia. CT development in the rural sector is not possible without addressing the current challenges identified in this study such as household heads farming experience, household size, and access to extension services, high costs of adoption, labour costs, and size of land owned by a household head. To reach this goal, econometrics analysis was derived from cross-sectional data for a single time period of production. Probit and Tobit models were econometrically estimated to evaluate rate of adoption (i.e., participation in conservation techniques) and intensity of adoption (i.e., allocation of land for conservation techniques) by the interviewee farmers.